1991
DOI: 10.1037/0021-843x.100.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Familial prevalence and coaggregation of schizotypy indicators: A multitrait family study.

Abstract: Schizophrenic probands (n = 17), their first-degree relatives (n = 61), and medically and psychiatrically screened normal control subjects (n = 18) were studied with structured interviews for DSM-III Axis I disorders and schizotypal personality disorder, questionnaire measures of schizotypy, measures of smooth-pursuit eye movement dysfunction, and attention dysfunction. Schizophrenic subjects scored abnormally on essentially all measures. Relatives differed significantly from control subjects on most measures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
162
4
3

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(184 citation statements)
references
References 31 publications
15
162
4
3
Order By: Relevance
“…Anhedonia measured by the Psychosis Proneness scales and conceptually related scales is a substantially heritable trait (Berenbaum and McGrew 1993;Berenbaum et al 1990;Kendler et al 1991;Linney 2003;MacDonald et al 2001), is elevated in subjects with schizotypal personality disorder (Camisa et al 2005), and specifically predicts the later development of schizophrenia spectrum disorders in psychometric high-risk samples (Gooding et al 2005;Kwapil 1998). In addition, elevated anhedonia is frequently reported in patients' biological relatives Franke et al 1993;Grove et al 1991;Katsanis et al 1990;Kendler et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Anhedonia measured by the Psychosis Proneness scales and conceptually related scales is a substantially heritable trait (Berenbaum and McGrew 1993;Berenbaum et al 1990;Kendler et al 1991;Linney 2003;MacDonald et al 2001), is elevated in subjects with schizotypal personality disorder (Camisa et al 2005), and specifically predicts the later development of schizophrenia spectrum disorders in psychometric high-risk samples (Gooding et al 2005;Kwapil 1998). In addition, elevated anhedonia is frequently reported in patients' biological relatives Franke et al 1993;Grove et al 1991;Katsanis et al 1990;Kendler et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The promise of examining correlations between personality features and neurocognitive performance measures to elucidate the structure of schizotypy is illustrated in studies by Kendler et al (1991) with a population-based sample of twins, and by Grove et al (1991) and Vollema and Postma (in press) with firstdegree relatives of schizophrenic patients. While these studies did not combine personality features and neurocognitive performance indices in factor analytic solutions, each found that neurocognitive indices were significantly related to individual dimensions of schizotypal signs and symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Kendler et al (1991) found that attentional dysfunction (indexed by the first principal component from eight neuropsychological tests emphasizing attention) was significantly related to a negative schizotypy dimension in twins from the general population. Among relatives of schizophrenic probands, Grove et al (1991) found that Degraded Stimulus Continuous Performance Test (DS-CPT) signal/noise discrimination scores had significant correlations with self-report Perceptual Aberration and Physical Anhedonia scores and a tendency Maier et al, 1999). toward higher correlations with the social-interpersonal component (negative schizotypy) than with the cognitive -perceptual component (positive schizotypy) of schizotypal personality disorder.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to consistent findings of high correlations within families of psychotic, schizophrenic, and schizotypal symptoms (Grove, Lebow, Clementz, Cerri, Medus & Iacono, 1991), no reports of explicit hallucinations are given for Wilson's first-degree relatives, nor does there seem to be any family history of such psychotic qualities. However, there is strong evidence of other forms of psychological disorder among Wilson's close family, implicating a potential genetic vulnerability to psychopathology, even if there is heterogeneity in symptom presentation.…”
Section: Family Effects and The Wilsons Geneticsmentioning
confidence: 60%